Impact of the frequency of plasma viral load monitoring on treatment outcomes among children with perinatally acquired HIV. Issue 6 (9th June 2019) - Sudjaritruk, Tavitiya; Boettiger, David C; Nguyen, Lam Van; Mohamed, Thahira J; Wati, Dewi K; Bunupuradah, Torsak; Hansudewechakul, Rawiwan; Ly, Penh S; Lumbiganon, Pagakrong; Nallusamy, Revathy A; Fong, Moy S; Chokephaibulkit, Kulkanya; et al.
Abstract: Introduction: Recommendations on the optimal frequency of plasma viral load (pVL) monitoring in children living with HIV (CLWH) who are stable on combination antiretroviral therapy (cART) are inconsistent. This study aimed to determine the impact of annual versus semi‐annual pVL monitoring on treatment outcomes in Asian CLWH. Methods: Data on children with perinatally acquired HIV aged <18 years on first‐line, non‐nucleoside reverse transcriptase inhibitor‐based cART with viral suppression (two consecutive pVL <400 copies/mL over a six‐month period) were included from a regional cohort study; those exposed to prior mono‐ or dual antiretroviral treatment were excluded. Frequency of pVL monitoring was determined at the site‐level based on the median rate of pVL measurement: annual 0.75 to 1.5, and semi‐annual >1.5 tests/patient/year. Treatment failure was defined as virologic failure (two consecutive pVL >1000 copies/mL), change of antiretroviral drug class, or death. Baseline was the date of the second consecutive pVL <400 copies/mL. Competing risk regression models were used to identify predictors of treatment failure. Results: During January 2008 to March 2015, there were 1220 eligible children from 10 sites that performed at least annual pVL monitoring, 1042 (85%) and 178 (15%) were from sites performing annual (n = 6) and semi‐annual pVL monitoring (n = 4) respectively. Pre‐cART, 675 children (55%) had World Health Organization clinical stage 3 or 4, the median nadir CD4 percentage was 9%, and the median pVL was 5.2 log10 copies/mL. At baseline, the median age was 9.2 years, 64% were on nevirapine‐based regimens, the median cART duration was 1.6 years, and the median CD4 percentage was 26%. Over the follow‐up period, 258 (25%) CLWH with annual and 40 (23%) with semi‐annual pVL monitoring developed treatment failure, corresponding to incidence rates of 5.4 (95% CI: 4.8 to 6.1) and 4.3 (95% CI: 3.1 to 5.8) per 100 patient‐years of follow‐up respectively ( p  =   0.27). In multivariable analyses, the frequency of pVL monitoring was not associated with treatment failure (adjusted hazard ratio: 1.12; 95% CI: 0.80 to 1.59). Conclusions: Annual compared to semi‐annual pVL monitoring was not associated with an increased risk of treatment failure in our cohort of virally suppressed children with perinatally acquired HIV on first‐line NNRTI‐based cART.